STUDENT TALK IN ENGLISH CLASSROOM INTERACTION AT SMA NEGERI 2 BINJAI - Windi Love Pita Sari; Busmin Gurning; Willem Saragih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2017)
This study was aimed at finding out the types of student talk, the dominant type of student talk and the reasons why the students used the dominant type of student talk during teaching-learning process at SMA Negeri 2 Binjai in 2016/2017 academic year. This qualitative research used 40 students in grade XII as the source data and the researcher used audio recording, observational tally sheet, and matrix as the instruments for collecting data. The data got by using Flanders Interaction Analysis Category (FIAC). The analysis showed that students were still passive in speaking in the classroom interaction. The total percentage of student talk was 36,44%. The percentages of student talk in the first meeting were: 11,63% of student talk-response and 9,42% of student talk-initiation. Then, the percentages of student talk in the second meeting were: 11,35% for student talk-response and 4,04% for student talk-initiation. The dominant type of student talk was student talk-response by 22,98%. The researcher found the reasons by interviewing the students. The reasons why the students used the dominant type student talk-response were: (a) responding to the teacher’s question was the obligation of the students, (b) the students were understood and interested with the topic, (c) the students want to increase their ability in speaking English because the students seldom speak English outside of classroom, (d) some students do not speak confidently in the class, so by responding to the teacher will build up their confidence, (e) the students want to increase their ability in speaking English in order to build up their confidence, (f) by responding to the teacher’s question, it made the students more active in the classroom. Keywords: classroom interaction, student talk, Flanders Interaction Analysis Category (FIAC).